(untitled) - Samajova, Veronika; David, Andrej; Zarnay, Pavel (Doprava a spoje, 2008)
The company Cesko-saske pristavy (CSP) was established on 1st October 2002 by Sachsische Binnenhafen Oberelbe (SBO). After the shipping company Ceskoslovenska plavba labska had bankrupted in 2002 SBO took over its two inland ports in the Czech Republic (the port of Decin and Lovosice). CSP owns and operates these ports, cooperates on logistics chains with SBO